2006
DOI: 10.1111/j.1439-0450.2006.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Competitive ELISA Kit for the Serological Diagnosis of Ovine, Caprine and Bovine Brucellosis

Abstract: A competitive ELISA (Brucella-Ab c-ELISA) was standardized and validated for the detection of Brucella antibodies in cattle, sheep and goat sera using a monoclonal antibody (MAb 4B5A) produced against Brucella melitensis biotype 2. The specificity and sensitivity of the assay were 100% to a 67.5% cut-off point (B/Bo%). When compared with an indirect ELISA, the Brucella-Ab c-ELISA did not demonstrate cross-reactions when testing positive sera for antibodies to some Enterobacteriaceae. A comparison was made betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
4
12
0
Order By: Relevance
“…The very high accuracy of c-ELISA that we found in this study is in agreement with previous findings (Portanti et al, 2006). Indeed, although FPA was shown as an accurate and rapid test, c-ELISA appears to be the superior in terms of Se, which is a critical factor in the eradication of B. melitensis in Southern Italy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The very high accuracy of c-ELISA that we found in this study is in agreement with previous findings (Portanti et al, 2006). Indeed, although FPA was shown as an accurate and rapid test, c-ELISA appears to be the superior in terms of Se, which is a critical factor in the eradication of B. melitensis in Southern Italy.…”
Section: Discussionsupporting
confidence: 81%
“…Accuracy of FPA was, then, compared with that of c-ELISA, which is a currently available, rapid test, which was previously proposed for improving accuracy and reducing costs of antibody testing for small ruminant brucellosis in Italy (Portanti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…screening tests are known to be caused by unrelated Enterobacteriaceae [26-35] and CELISA can eliminate such reactions [33]. B. abortus vaccination strain 19 also gives rise to an antibody response similar to that resulting from natural infection [33] but CELISA can eliminate this false-positive reaction only by approximately 50% [36]. In our study, 9/177 (5.1%) of farms held vaccinated cattle and the CELISA positive reactions of vaccinated cows in two farms might be due to the false-positive reactions with B. abortus vaccination strain S19.…”
Section: Discussionmentioning
confidence: 99%
“…1 Representative results of the NERIFA using positive and negative serum samples present study was performed with undiluted well-identified bovine and ovine sera. The NERIFA model was first optimized by using a mouse monoclonal anti-Brucella LPS antibody (clone 4B5A, Portanti et al 2006) and a few number of Brucella antibody positive and negative sera. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%